2012
DOI: 10.1523/jneurosci.3080-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Maturation of Goal-Directed Behavior and Dopaminergic Systems during Adolescence

Abstract: Adolescence is a crucial developmental period characterized by specific behaviors reflecting the immaturity of decision-making abilities. However, the maturation of precise cognitive processes and their neurobiological correlates at this period remain poorly understood. Here, we investigate whether a differential developmental time course of dopamine (DA) pathways during late adolescence could explain the emergence of particular executive and motivational components of goal-directed behavior. First, using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
220
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(235 citation statements)
references
References 65 publications
8
220
6
1
Order By: Relevance
“…Dopamine synaptic connectivity undergoes intense dynamic changes in striatal regions during adolescence (Spear, 2000;Antonopoulos et al, 2002;McCutcheon et al, 2012;Naneix et al, 2012). In this experiment, we were not able to identify the differences in dopamine connectivity in the NAcc between adult mice treated with amphetamine or saline during adolescence.…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 83%
See 1 more Smart Citation
“…Dopamine synaptic connectivity undergoes intense dynamic changes in striatal regions during adolescence (Spear, 2000;Antonopoulos et al, 2002;McCutcheon et al, 2012;Naneix et al, 2012). In this experiment, we were not able to identify the differences in dopamine connectivity in the NAcc between adult mice treated with amphetamine or saline during adolescence.…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 83%
“…In rodents, the dopamine innervation to the medial prefrontal cortex (mPFC) increases progressively beyond the weaning stage until early adulthood, with substantial modifications in fiber density, shape, and organization happening during adolescence (Kalsbeek et al, 1988;Benes et al, 2000;Manitt et al, 2011;Naneix et al, 2012). In parallel to these changes in dopamine circuitry, local mPFC neurons shift towards a mature state of responsiveness to the modulatory effects of dopamine (Spear, 2000;Tseng and O'Donnell, 2007;O'Donnell, 2011;Cass et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies using juvenile rats showed that dopamine plays a prominent role in regulating inhibitory tone in the mPFC (Seamans et al, 2001, partially through altering the excitability of interneurons (Gorelova et al, 2002;Trantham-Davidson et al, 2004). Later, it was found that there are significant changes in the expression of PFC dopamine receptors throughout adolescent development (Andersen et al, 2000;Brenhouse et al, 2008;Naneix et al, 2012) and accordingly, the dopaminergic regulation of inhibition has been shown to be influenced by age (Paul and Cox, 2013). The delayed maturation of dopamine's function in the mPFC is also consistent with the finding that prefrontal GABAergic cells increase their responsiveness to dopamine receptor stimulation during adolescent development.…”
Section: Introductionmentioning
confidence: 99%
“…The adolescent striatum is still immature with ongoing multiple remodelling processes, for example, in presynaptic dopaminergic innervation (Mathews et al 2009;Matthews et al 2013;Naneix et al 2012;Stamford 1989), and dopaminergic (Andersen et al 2000;Naneix et al 2012;Tarazi and Baldessarini 2000;Tarazi et al 1998;Teicher et al 1995) and endocannabinoid receptors (de Fonseca et al 1993;Klugmann et al 2011). Therefore, I…”
Section: Risperidone-induced Changes In Catalepsy: Adolescents Vs Adultsmentioning
confidence: 99%
“…In adolescents, presynaptic dopaminergic innervation of the striatum, as identified by TH levels, is still incomplete (Matthews et al 2013). This may explain why the adolescent striatum has lower levels of dopamine release both at baseline (Naneix et al 2012) and after stimulation (Matthews et al 2013;Stamford 1989) compared to adults. Consistent with this, adolescent rats show lower levels of striatum-mediated stereotypic fine movements in response to acute amphetamine (Matthews et al 2013).…”
Section: Risperidone-induced Behavioural Changes In Adolescents Vs Admentioning
confidence: 99%